ChemInform Abstract: Reductive Ullmann Coupling of Aryl Halides by Palladium Nanoparticles Supported on Cellulose, a Recoverable Heterogeneous Catalyst. Issue 51 (17th December 2013) - Rasouli, Mohammad Ali; Ranjbar, Parviz Rashidi
Abstract Palladium nanoparticles supported on cellulose are shown to act as catalyst for the reductive Ullmann coupling of aryl halides.